The Role of Indonesian Language as a National Language: Bahasa Indonesia - Alwan, Henry; Audina Pratiwi, Deswita; Ramafasalbi, Rafli; Veny Indrasih , Juliyanti; Repelita, Tridays (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze the role of Indonesian as the national language in various aspects of life in Indonesia. Using qualitative descriptive methods, data was collected through semi-structured interviews and observations, and analyzed using thematic analysis techniques. Normality tests with Kolmogorov-Smirnov and Shapiro-Wilk showed that the data were normally distributed, while Levene's test confirmed the homogeneity of variance between data groups. The research results show that Indonesian plays an important role in the field of education as the main language of instruction, facilitating government and administration as an official language, and supporting economic growth through facilitating business transactions and promoting local products. In a socio-cultural context, Indonesian is a medium of artistic expression and an important tool in intercultural dialogue, strengthening the nation's cultural identity. This research emphasizes the important role of Indonesian in uniting the nation, facilitating communication, supporting education and government, and strengthening national identity. Continuous efforts are needed to maintain and develop the use of Indonesian so that it continues to play a vital role in the development and unification of the nation.